Determination of Dopamine in Hypoxanthine System with Glassy Carbon Mercury Film Electrode - LIAN, KAOQI; KANG, WEIJUN; LI, SHAN (Asian Journal of Chemistry, 2010)
The electrochemical behaviour of glassy carbon mercury film electrode in hypoxanthine solution and its electrocatalytic oxidation for dopamine in this solution were studied. It indicated, by adding certain amount of hypoxanthine in electrolyte solution, it had good inhibition on the stripping peak of Hg at higher potentials and the electrode showed a better stability in the solution. In pH 1.81 buffer solution, the reduction peak of dopamine was almost unchanged when ascorbic acid coexisted, the reduction peak current of dopamine was proportional to its concentration in the range of 1.5 × 10-5–5.6 × 10-4 mol L-1 and the detection limit could reach 2 × 10-6 mol L-1. The method could obtain better result when it applied to the determination dopamine in synthetic sample.